Effects of S-Curve Runs and Sprint In-Out Exercise Methods Against The Increase of Speed, in 100 Meters Sprint Observed from Foot Length and Height Ratios - Ridwan Sinurat; Masdi Janiarli (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The purpose of this study was to find the effect of differences between S-Curve Runs and Sprint In-Out exercise methods against the increase of speed in 100 meters sprint; the different increases of speed in 100 meters sprints for the runners with big, medium, and small ratios of foot length and height; and the differences of interactions between S-Curve Runs and Sprint In-Out exercise methods and foot length and height ratios against the increase of speed in 100 meters sprint. This research was conducted at Chevron Football School in Pekanbaru for 8 weeks by using the experimental method of 2 x 3 factorial designs. The research population contained students of the school. Purposive Random Sampling was utilized as the sampling method included 42 students with big, medium, and small ratios of foot length and height, for each took 14 students as the samples. ANOVA was employed as the data analysis technique. Prerequisite tests of data analysis were conducted beforehand by using the sample normality test (Lilliefors Test at α = 0.05) and homogeneity of variance test (Bartlett’s Test at α = 0.05). Results of data analysis indicated that there were significant differences between S-Curve Runs and Sprint In-Out exercise methods against the increase of speed in 100 meters sprint with Fcount = 10.54758 > Ftable = 4.07 in which the effects of S-Curve Runs exercise have better improvement than Sprint In-Out exercise, with the average increases for each are 2.17 and the 1.7; there were significant differences between the runners with big, medium, and small ratios of foot length and height with Fcount = 14.16068 > Ftable = 3.22. The increase of 100 meters sprint result on samples with big ratios of foot length and height was better than samples with medium and small ratios, for each having average increase of 2:43, 1.89 and 1:51; and there was no correlation effect between the S-Curve Run and Sprint In-Out training methods and the foot length and height ratios against the increase of running speed, in which the Fcount = 0.29174 < Ftable = 3:22.